Stromal cells from human decidua exert a strong inhibitory effect on NK cell function and dendritic cell differentiation. - Daniele Croxatto; Paola Vacca; Francesca Canegallo; Romana Conte; Pier Luigi Venturini; Lorenzo Moretta; Maria Cristina Mingari (PLoS ONE)
Stromal cells (SC) are an important component of decidual tissues where they are in strict proximity with both NK and CD14(+) myelomonocytic cells that play a role in the maintenance of pregnancy. In this study we analyzed whether decidual SC (DSC) could exert a regulatory role on NK and CD14(+) cells that migrate from peripheral blood (PB) to decidua during pregnancy. We show that DSCs inhibit the IL15-mediated up-regulation of major activating NK receptors in PB-derived NK cells. In addition, the IL15-induced NK cell proliferation, cytolytic activity and IFN-γ production were severely impaired. DSCs sharply inhibited dendritic cells differentiation and their ability to induce allogeneic T cell proliferation. Indoleamine 2,3-dioxygenase (IDO) and prostaglandin E2 (PGE2) mediated the inhibitory effect of DSCs. Our results strongly suggest an important role of DSCs in preventing potentially dangerous immune response, thus contributing to maintenance of pregnancy.